Primary Nasal Reconstruction in Self-Inflicted Nasal Injury. Issue 7 (October 2015) - Kapadia, Abizer; John, Jerry R.; Gaba, Sunil; Sharma, Ramesh Kumar
Abstract : Abstract: Self-inflicted injury of the nose is extremely rare. It may be associated with severe psychopathology and suicidal ideation. The authors report a case of a 24-year-old man, who presented with soft-tissue loss over both the alae of his nose. He had cut off the alar rims with an ordinary razor blade. He was overtly concerned about his nose being excessively broad and fat. A diagnosis of body dysmorphic disorder with nonsuicidal self-injury was made. Patient was observed during 72 hours in hospital with psychiatric support and local dressings. The authors undertook primary nasal reconstruction with nasolabial flaps on both sides for coverage. In conclusion, self-inflicted nasal injury mandates a judicious balancing of psychiatric support and surgical reconstruction. This can prevent untoward sequelae including further self-harm and suicide.